Green-Synthesized Silver Nanoparticles Using Filipendula ulmaria (L.) Maxim. and Salvia verticillata L. Extracts Inhibit Migration and Modulate Redox Homeostasis in Human Breast Cancer Cells via Nrf-2 Signaling Pathway - Matić, Miloš; Obradović, Ana; Paunović, Milica; Ognjanović, Branka; Mihailović, Vladimir; Srećković, Nikola; Stanković, Milan (Antioxidants, 2025)
Breast cancer is a leading cancer diagnosis for women around the world, with a variable degree of curability. Conventional chemotherapeutic treatments often induce toxicity and damage to healthy tissues, as well as the development of drug resistance, which is why an increasing number of new therapeutic regimens focus on the use of natural products and various modifications of their delivery to target tissues. Silver nanoparticles possess unique physicochemical characteristics, notably their increased surface area, suggesting that they hold significant potential for biomedical applications. This research evaluates the capacity of silver nanoparticles green synthesized with aqueous extracts of Filipendula ulmaria (FUAgNPs) and Salvia verticillata (SVAgNPs) to alter migration and redox homeostasis in the human breast cancer cell line MDA-MB-231. To determine the values of redox homeostasis parameters, the cells were treated with five different concentrations (5, 10, 20, 50, and 100 μg/mL) for 24 h and 72 h, while to test the migratory potential and concentrations of matrix metalloproteinase-9 (MMP-9) and nuclear factor erythroid 2–related factor 2 (Nrf-2), the cells were treated at two concentrations (5 and 50 µg/mL) for 72 h. The obtained results indicate increased production of superoxide anion radicals, malondialdehyde (MDA), and nitrites after the investigated treatment on MDA-MB-231 cells. The treatments induced only a slight elevation in Nrf-2 levels, which correlates with weak de novo synthesis of reduced glutathione (GSH), suggesting that the tested nanoparticles weaken the inherent antioxidative systems of the tested cells. The migration potential of cells was significantly reduced, and MMP-9 concentration was significantly inhibited. Based on the demonstrated antitumor effect, confirmed by the reduced migratory potential of the examined cells and disrupted redox balance, these nanoparticles have potential for additional investigation with the aim of improving the efficacy of antitumor therapy. Also, FUAgNPs and SVAgNPs possess the capacity to be potentially promising novel chemotherapeutic agents against breast cancer progression and metastasis.